Analisis Produktivitas Pekerjaan Struktur Beton Bertulang Pada Proyek Gedung Polda Riau 2018 - Putra, Muhammad Oki Pirdana; Iriana, Rian Trikomara; Malik, Alfian (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Productivity affects the project progresses between actual field and the planned schedule of the construction project. Therefore, the level of productivity at crisis activity in a schedule planning project which in this case is structure project needs to be analyzed. This study aims to analyze actual productivity on the field and determine the factors affecting productivity towards the construction project of Regional Police Department of Riau. The value of actual work productivity is obtained through direct observation on the field using the method of Time Study. The data is analyzed and converted into field index, then compared with SNI 7394 : 2008 index as standard reference. Base on result of calculation, the work productivity value of plate, column, and beam formwork respectively are 19.99 m2/hour, 10.91 m2/hour, and 4.89 m2/hour with their index values respectively are 0.10 MH, 0.26 MH, and 0.37 MH. Next, the work productivity value of plate, column, and beam reinforcement respectively are 516.77 kg/hour, 187.61 kg/hour, and 187.91 kg/hour with their index values respectively are 0.01 MH, 0.03 MH, and 0.02 MH. For plate, column, and beam casting, their work productivity value respectively are 13.21 m3/hour, 12.98 m3/hour, and 13.53 m3/hour with their index value respectively are 0.28 MH, 0.24 MH, and 0.26 MH. In conclusion, the field index value are less compared than SNI 2008 index.Keywords: Productivity, Crisis activity, Time study, Index, SNI 7394 : 2008